The structure and control method of hybrid power source for electric vehicle. (1st October 2016) - Li, Maobing; Xu, Hui; Li, Weimin; Liu, Yin; Li, Fade; Hu, Yue; Liu, Li
Abstract: In this paper, an electric vehicle powertrain configuration is presented, which the lithium-ion battery integrated with ultracapacitors is developed as the hybrid power system to improve the transient performance of an electric vehicle, and to decrease the damage to the battery pack. In the proposed system, a bidirectional direct current/direct current converter is used to couple the ultracapacitors bank to the main battery pack. The energy management strategy based on fuzzy logic for hybrid power system has been proposed to promote the performance of energy flow in the electric vehicle. The experiment results in urban driving cycles show remarkable advantages of the proposed hybrid system configuration and energy management strategy. About 30% of the battery capacity energy is saved while using the hybrid power source. Besides, the voltage and current curves of battery become smoother than that with the single power. Highlights: A hybrid power source electric vehicle powertrain configuration is presented. The energy management strategy based on fuzzy logic is proposed. The experiment results show remarkable advantages of the configuration and method.